Effects of Window Films in Thermo-Solar Properties of Office Buildings in Hot-Arid Climates - Sedaghat, Ahmad; Abbas Oloomi, Seyed Amir; Malayer, Mahdi Ashtian; Alkhatib, Fadi; Sabri, Farhad; Sabati, Mohammad; Salem, Hayder; Zafar, Waqar Jan; Mostafaeipour, Ali; Issakhov, Alibek; Jahangiri, Mehdi; Techato, Kuaanan; et al. (Frontiers in Energy Research, 2021)
The electricity consumption in residential/office buildings corresponded to 45% of the total annual electricity demand in hot-arid climates. This accounted for 27.2 TWh of electricity consumption with 14.2 MWh/capita/year in Kuwait. In this research, four offices in an educational building were equipped with a meteorological data logging system using temperature, humidity, and illuminance sensors. All four offices had double-glazed windows. Moreover, two offices were equipped with two types of commercially available window films. Two million data were stored in iCloud using Wi-Fi and an Internet of Things (IoT) system for the 3 months of June, July, and August 2019. In our previous published paper in Solar Energy, the results for June 2019 were analyzed using an explicit less accurate rational PDF function. Here, histograms and temperature/humidity are analyzed more accurately by numerical kernel density estimation (KDE) functions and compared for the two offices with/without 3M Neutral 20 window films for 3 months of June, July, and August 2019. Two floors of the same building consisting of 31 offices were also modeled and simulated in Design Builder to study energy saving and CO2 footprint reduction using various window films. Two floors of the same building consisting of 31 offices were also modeled and simulated to study energy saving and CO2 footprint reduction using various window films. The results of simulations for the month of July 2019 using SOL 101 and SOL 102 window films, respectively, showed that about 250 kg and 255 kg of production of CO2 could be reduced and energy saving counted for 416 and 422 kWh. Measurements from offices with 3M Neutral 20% and 3M Neutral 70% window films for the month of July 2019 indicated that the carbon footprint could be reduced by about 82 kg and 0.43 kg and energy saving counted for 147.11 and 0.71 kWh, respectively. It was observed that an annual energy saving and CO2 footprint reduction of 2.76% could be achieved using window films in a hot-arid climate.